Perception of predation risk by tamarins and marmosets crossing bridges over a pipeline right-of-way strip in the Atlantic forest of Brazil - López-Ramirez, Luis; Lucas, Priscila; Aguiaro Pereira, Talita de Azevedo; Ruiz-Miranda, Carlos R. (Frontiers in Conservation Science, 2024)
One of the negative effects of linear infrastructures is the formation of barriers to the movements for arboreal wildlife resulting in the reduction in connectivity between populations and thus increasing the risk of extinction. One of the most widely used ways to mitigate these barrier effects is canopy bridges. There is a lack of knowledge about how behavioral differences between species may affect the efficacy of canopy bridges. The purpose of this study was to evaluate the hypothesis that Leontopithecus rosalia (an endangered endemic species) and Callithrix spp. hybrids (introduced invasive species) perceive canopy bridges as sites with risk of predation. We compared the behavior of these species during attempts to cross four canopy bridges installed over oil and gas pipeline right-of-way strips, and another 4 bridges installed inside the forest near the pipeline bridges. The behavior was recorded from 30-second videos obtained from two camera traps installed at each end of the bridges. Of the 1917 crossing events identified, 356 events were randomly chosen for behavioral data collection. Of these, 173 were social group crossing events and 183 individual crossing events. There were few crossings (7.9%) with the two species present. The differences between the species were more quantitative than qualitative and may be related to interspecific differences in vulnerability to predation and anti-predatory tactics. Both species exhibited significantly more behaviors related to perception of risk of predation (vigilance, hesitation, rapid passage) in the pipeline bridges than in the forest bridges. One vigilance measure showed higher occurrence during the first months after installation of the cameras, especially for Callithrix spp., but in general there was little waning of the risk-assessment response. Alarm calls, scent marking and social and feeding behaviors were rare or absent. Low-cost simple canopy bridges may be an effective strategy to overcome the barrier effect of right-of-way strips over gas and oil pipelines. However, the results on perceived risk of predation raise the hypothesis that there may be a cost-benefit ratio between distance to be traveled and risk perception that would lead to a reduction in effectiveness of bridges in greater distance. We discuss the implications for conservation of an endangered species and management of an invasive species.